Current Views of Toll-Like Receptor Signaling Pathways - Masahiro Yamamoto; Kiyoshi Takeda (Gastroenterology Research and Practice)
On microbial invasion, the host immediately evokes innate immune responses. Recent studies have demonstrated that Toll-like receptors (TLRs) play crucial roles in innate responses that lead not only to the clearance of pathogens but also to the efficient establishment of acquired immunity by directly detecting molecules from microbes. In terms of intracellular TLR-mediated signaling pathways, cytoplasmic adaptor molecules containing Toll/IL-1R (TIR) domains play important roles in inflammatory immune responses through the production of proinflammatory cytokines, nitric oxide, and type I interferon, and upregulation of costimulatory molecules. In this paper, we will describe our current understanding of the relationship between TLRs and their ligands derived from pathogens such as viruses, bacteria, fungi, and parasites. Moreover, we will review the historical and current literature to describe the mechanisms behind TLR-mediated activation of innate immune responses.